Design of an 845-nm GaAs Vertical-Cavity Silicon-Integrated Laser with an Intracavity Grating for Coupling to a SiN Waveguide Circuit - Sulakshna Kumari; Johan Gustavsson; Emanuel P. Haglund; Jorgen Bengtsson; Anders Larsson; Gunther Roelkens; Roel Baets (IEEE Photonics Journal, 2017)
A short-wavelength hybrid GaAs vertical-cavity silicon-integrated laser (VCSIL) with in-plane waveguide coupling has been designed and optimized using numerical simulations. A shallow etched silicon nitride (SiN) grating is placed inside the cavity of the hybrid vertical-cavity silicon-integrated laser to both set the polarization state of the resonant optical field and to enable output coupling to a SiN waveguide with high efficiency. The numerical simulations predict that for apertures of 4 and 6- $μ\text{m}$ oxide-confined VCSILs operating at 845-nm wavelength, a slope efficiency for the light coupled to the waveguide of 0.18 and 0.22 mW/mA is achievable, respectively, while maintaining a low threshold gain of 583 and 589 cm −1, respectively, for the lasing.